Find (f∘g)(x).

f(x)=4x–1
g(x)=2x2–3x+4
Write your answer as a polynomial in simplest form.
(f∘g)(x)=

1 answer

To find (f∘g)(x), we need to substitute the expression for g(x) into f(x):

f(g(x)) = 4(2x^2-3x+4) - 1

Multiplying through, we get:

f(g(x)) = 8x^2 - 12x + 16 - 1

Simplifying, we have:

(f∘g)(x) = 8x^2 - 12x + 15
Similar Questions
    1. answers icon 20 answers
  1. 1. Divide. Write your answer in simplest form.2/3 / 1/4 2. Find the product. 1/2 x 3/7 3. Divide. Write the quotient in simplest
    1. answers icon 18 answers
  2. a)Find a Cartesian equation relating and corresponding to the parametric equations: x=2sin(3t), y=9cos(3t). Write your answer in
    1. answers icon 2 answers
  3. Find the product. Your answer should be in simplest form.1. one-third• 7 (1 point) one over twenty-one two and one-seventh two
    1. answers icon 72 answers
more similar questions